The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/nop2.474
|View full text |Cite
|
Sign up to set email alerts
|

Nursing care for older patients with pressure ulcers: A qualitative study

Abstract: Aim To explore the experience and perception of pressure ulcers in a group of nurses caring for older patients. Design A qualitative study based on interviews with (N = 6) nurses working with older patients. Method A qualitative approach was applied using thematic analysis influenced by Braun and Clarke. Results The findings comprised one main theme “Prevention of pressure ulcers is important” and four sub‐themes “Nursing resources on the ward,” “Basic nursing skills—lift the duvet,” “Introduction of new nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
3
4
0
2
Order By: Relevance
“…Nurses in this study elucidated the leading role they had in PIP. This is consistent with previous studies that most nurses perceived that they took the most responsibility in preventing PIs development in hospitals and long‐term care settings (Garrigues et al, 2017; Lindhardt et al, 2020; Tan et al, 2020). Reasons could be that first‐line nurses had the most frequent contact with patients; had specific skin care knowledge (Tan et al, 2020); and placed positive attitudes and a high value on PIP in their daily work (Lindhardt et al, 2020; Samuriwo, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nurses in this study elucidated the leading role they had in PIP. This is consistent with previous studies that most nurses perceived that they took the most responsibility in preventing PIs development in hospitals and long‐term care settings (Garrigues et al, 2017; Lindhardt et al, 2020; Tan et al, 2020). Reasons could be that first‐line nurses had the most frequent contact with patients; had specific skin care knowledge (Tan et al, 2020); and placed positive attitudes and a high value on PIP in their daily work (Lindhardt et al, 2020; Samuriwo, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies that most nurses perceived that they took the most responsibility in preventing PIs development in hospitals and long‐term care settings (Garrigues et al, 2017; Lindhardt et al, 2020; Tan et al, 2020). Reasons could be that first‐line nurses had the most frequent contact with patients; had specific skin care knowledge (Tan et al, 2020); and placed positive attitudes and a high value on PIP in their daily work (Lindhardt et al, 2020; Samuriwo, 2010). However, Sving et al (2012) in their study of PI prevention in Sweden found PIP was a task delegated to assistant nurses who were responsible for assessment and intervention implementation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The rationale behind these protocols is founded on the understanding that a proactive, multidisciplinary approach is essential for the effective prevention of pressure injuries. 16,17 During neurosurgical procedures, continuous monitoring of the patient's neurological status is paramount to ensuring the safety and efficacy of the surgery. This encompasses real-time surveillance of neurologic functions as well as the maintenance of normothermia to support neuronal health and minimize the risk of perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant medical expenditure and caregiver stress causes an immense social and family burden ( 2 , 11 ). The risk factors for pressure sores include older age, immobility, multiple comorbidities, and malnutrition ( 12 ). Although prevention costs of pressure sores are far lower than treatment costs, effective prevention and control requires the construction of a comprehensive pressure sore management system and feasible work flow to achieve pressure sore monitoring standardization and proceduralization ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%